Paradigma dan Pemikiran Filsuf Islam dalam Filsafat Ilmu dan Pendidikan Islam - Syifa’yah, Lilis; Hasanah, Syofiatul; Arif, Abd. Jalil (TSAQOFAH, 2026)
Although Islamic philosophy of knowledge and education has been widely studied, systematic research that explicitly integrates the thought of Muslim philosophers as a philosophical foundation for developing a holistic model of Islamic education remains limited. This study aimed to describe the views of classical and contemporary Muslim philosophers on the philosophy of knowledge and to explain their relevance for formulating a comprehensive Islamic education that encompasses intellectual, moral, and spiritual dimensions. A qualitative approach with a descriptive literature study design was employed through a review of scholarly literature on the philosophy of knowledge, education, and the ideas of key Islamic thinkers such as Al-Farabi, Ibn Sina, and Al-Ghazali. Data analysis involved reduction, presentation, and synthesis to identify the main themes. The findings indicate that Islamic education should integrate revelation, reason, and empirical experience by employing a variety of learning methods—demonstrative, dialectical, empirical, ma'rifah, historical-sociological, and qiyās—to cultivate human beings who are intellectually, morally, and spiritually balanced. These findings provide theoretical and methodological contributions to the development of a holistic Islamic education curriculum and open opportunities for further empirical research on the implementation of these principles in diverse contemporary Islamic educational settings.